Effect of annealing temperature on the electrical properties of HfAlO thin films. (16th January 2019) - Lin, Hongxiao; Li, Chun; He, Zhiwei
Abstract : High‐K gate dielectric HfAlO thin films with different temperature annealing treatment have been deposited on the Si substrate by atomic layer deposition. The electrical properties of Hf‐films are analysed by measurement of high‐frequency capacitance–voltage ( C – V ) and leakage current density–voltage ( J–V ) characteristics. The electrical measurement results indicate the decrease of equivalent oxide thickness (EOT) due to the great change of microstructure and densification after high temperature annealing and the increase of permittivity. However, the interface state density increases. Moreover, the leakage current increases with the increase of annealing temperature. The HfAlO film annealed at 650°C has the best electrical parameters, such as dielectric constant, EOT and leakage current density determined through capacitance–voltage and current density–voltage measurements were 23.5, 0.84, 6.8 × 10 −7 mA·cm −2, respectively.